Agricultural extension messages using video on portable devices: Increase knowledge about seed selection and seed storage and handling among smallholder potato farmers in southwestern Uganda - Van Campenhout, Bjorn; Vandevelde, Senne; Walukano, Wilberforce; Van Asten, Piet (International Food Policy Research Institute, 2016)
To feed a growing population, agricultural productivity needs to increase dramatically. Agricultural extension information, with its public, non-rival nature, is generally undersupplied, and public provision remains challenging. In this research, we explore the effectiveness of alternative modes of agricultural extension information delivery. We test whether simple agricultural extension video messages delivered through Android tablets increase knowledge of recommended practices in seed selection, storage, and handling among a sample of potato farmers in southwestern Uganda. Using a field experiment with ex ante matching in a factorial design, we find that showing agricultural extension videos significantly affects farmers’ knowledge. However, our results suggest impact pathways that go beyond simply replicating what was shown in the video. Video messages may also trigger a process of abstraction, whereby farmers apply insights gained in one context to a different context. Alternatively, video messages may activate knowledge farmers already posses but, for some reason, do not use.